Teachers’ Digital Literacy Communication Competence: A Meta-Analysis - Begimbetova, Guldana A.; Retnawati, Heri; Triyono, M.Bruri; Kassymova, Gulzhaina K.; Mumpuni, Kistantia Elok (Universitas Negeri Makassar, 2025)
This research aims to synthesize empirical findings on high school teachers' digital communication competence through a meta-analytic approach, addressing inconsistencies in existing literature and the urgent need to enhance educators' digital literacy. The study investigates the conclusions of 42 articles published between 2008 and 2022, focusing on the theme of digital communication competence. A systematic review was conducted using the PRISMA framework, involving a three-stage process of identification, screening, and inclusion of relevant studies. The analysis revealed a common true effect size across all studies, but significant variability in effect sizes, with a variance (τ²) of 421.92 and a standard deviation (τ) of 20.5408. The Q-Profile indicated substantial heterogeneity (Q=6090163.73, p=0, I²=100%), highlighting inconsistencies in the conclusions drawn from the pooled articles. Additionally, the funnel plot analysis showed skewness, indicating potential publication bias. These findings underscore the need for further research to explore the interaction between pedagogical and technological knowledge, ultimately aiming to improve digital communication competence among high school teachers. The study concludes that addressing these inconsistencies is crucial for developing effective strategies to enhance educators' digital literacy in an increasingly digital educational landscape.